Educação do Movimento dos Trabalhadores Sem Terra : um espaço de resistência à colonialidade e seus mecanismos de poder - Casallas, Yohana Marcela Sierra (2020)
This dissertation was developed within the research line Social Movements, Politics and Popular Education of the Graduate Program in Education (PPGE) of the Federal University of Mato Grosso (UFMT) with the support of the Coordination for the Improvement of Higher Level Personnel (CAPES). The research aims to analyze the pedagogical and educational initiatives developed in schools in the field, coordinated by the Landless Rural Workers Movement (MST) in Mato Grosso, as processes of resistance to coloniality and its power mechanisms. The proposed discussion raises several relevant issues of peasant educational history in Brazil, such as the transition from rural education to country education; the mediation between the movement and the government for the coordination and functioning of schools; and the emancipatory educational practices implemented in the schools of the MST settlements. This is a qualitative research, developed with the research tool: participatory action research (IAP). It is anchored in Latin American critical thinking and in the decolonial theoretical paradigm and relies on the political and pedagogical contributions of Paulo Freire and Roseli Caldart. It was developed together with teachers and managers of the Florestan Fernandes State School located in the Settlement 12 of October in the municipality of Claudia, State of Mato Grosso. The investigative techniques were: semi-structured interviews, participant observation and field diaries. The dissertation is divided into three chapters. In the first, it presents a theoretical contextualization about coloniality, decoloniality and decolonial proposals in the perception of different Latin American authors. The second one, indicates the current state of Latin American rural education, with emphasis on Colombia and Brazil. The socio-political and economic factors that qualify the rural school and the educational paradigm of the countryside are treated. The third and last chapter is dedicated to the analysis of the educational process of the MST, as a social movement fighting for popular agrarian reform. The results obtained make it possible to affirm that the MST has an educational political project that manages to break with the colonial structure present in the peasant schools through its philosophical and pedagogical principles, as well as its daily practice. Equally, it shows that the changes achieved in education for the peasant population in Brazil stem from the interventions of social movements in the educational and political agenda, specifically of the MST, which contemplated in its political project the creation of an education for peasants. The results obtained suggest that a possible educational proposal could be applied in similar contexts, such as in Colombia, where the paradigm of rural education is still very entrenched.